Tecia solanivora infestation increases tuber starch accumulation in Pastusa Suprema potatoes. Issue 11 (15th August 2018) - Kumar, Pavan; Garrido, Etzel; Zhao, Kun; Zheng, Yi; Alseekh, Saleh; Vargas‐Ortiz, Erandi; Fernie, Alisdair R.; Fei, Zhangjun; Poveda, Katja; Jander, Georg
Abstract: In response to infestation with larvae of the Guatemalan tuber moth ( Tecia solanivora ), some Solanum tuberosum (potato) varieties exhibit an overcompensation response, whereby the total dry mass of uninfested tubers is increased. Here, we describe early responses, within the first few days, of T. solanivora feeding, in the Colombian potato variety Pastusa Suprema. Non‐targeted metabolite profiling showed significant secondary metabolism changes in T. solanivora‐ infested tubers, but not in uninfested systemic tubers. In contrast, changes in primary metabolism were greater in uninfested systemic tubers than in the infested tubers, with a notable 80% decline in systemic tuber sucrose levels within 1 d of T. solanivora infestation. This suggested either decreased sucrose transport from the leaves or increased sink strength, i.e., more rapid sucrose to starch conversion in the tubers. Increased sucrose synthesis was indicated by higher rubisco activase and lower starch synthase gene expression in the leaves of infested plants. Elevated sink strength was demonstrated by 45% more total starch deposition in systemic tubers of T. solanivora‐ infested plants compared to uninfested control plants. Thus, rather than investing in increased defense of uninfested tubers, Pastusa Suprema promotes deposition of photoassimilates in the form of starch as a response to T. solanivora infestation. Abstract : Tecia solanivora (Guatemalan tuber moth) is a devastating pest of Solanum tuberosum (potato) in Latin America. However, within days after the infestation of a single tuber of a potato plant, elevated starch synthesis and deposition increases the size of uninfested tubers on the same plant, thereby increasing overall yield.